1998
DOI: 10.1007/s00585-998-0140-8
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric conductance distribution and MHD wave structure: observation and model

Abstract: Abstract. The ionosphere in¯uences magnetohydrodynamic waves in the magnetosphere by damping because of Joule heating and by varying the wave structure itself. There are dierent eigenvalues and eigensolutions of the three dimensional toroidal wave equation if the height integrated Pedersen conductivity exceeds a critical value, namely the wave conductance of the magnetosphere. As a result a jump in frequency can be observed in ULF pulsation records. This eect mainly occurs in regions with gradients in the Pede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…However, Allan [1983] did not have these techniques available. Budnik et al [1998] used time series and power spectra to examine data from one GOES satellite. It is not as easy to identify field line resonances solely from power spectra, especially when there is significant damping in the night hemisphere.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Allan [1983] did not have these techniques available. Budnik et al [1998] used time series and power spectra to examine data from one GOES satellite. It is not as easy to identify field line resonances solely from power spectra, especially when there is significant damping in the night hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…We have presented observations and simulations demonstrating the excitation of quarter‐wave modes near 0700 LT in June at L = 2.6 in the American sector. According to Allan and Knox [1979a, 1979b] and Budnik et al [1998], Σ A − Σ P should have different signs at conjugate ends of the field line when the quarter‐wave mode is generated. Figure 6a shows that the Pedersen conductance was larger than the Alfvén conductance at both ends of the field line when we observed these events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Budnik et al [1998] presented a satellite observation at L = 6.8 of a pulsation event with a sharp frequency change observed both in the radial and azimuthal magnetic perturbations which they proposed was due to the transformation of a half‐wavelength harmonic mode into a quarter‐wavelength mode as the Pedersen conductivities became increasingly asymmetric across the dawn‐dusk terminator. Although Budnik et al [1998] did not solve for the field‐aligned eigenmodes, they inferred that when the Pedersen conductivity at one end of the field line became less than a critical conductivity given by Σ P critical = 1/μ 0 A I where A I is the Alfvén speed at the ionosphere (Σ P critical = 0.35 S for their case) the mode would change from a half‐ to a quarter‐wavelength harmonic. They observed a sharp frequency change from 18–19 mHz to 5–6 mHz, which could be consistent with this mode change.…”
Section: Discussionmentioning
confidence: 99%
“…This event showed highly asymmetric amplitudes and a 90° phase difference between the D component magnetic fields at both ends of the field line. Investigating the influence of ionospheric conductance on wave reflection conditions, Budnik et al [] reported a pulsation event recorded by the GOES‐6 (geosynchronous) satellite, in which the wave frequency abruptly decreased from 18–19 to 5–6 mHz when the satellite was crossing the dusk terminator. They explained this jump in frequency as a change in the wave structure.…”
Section: Introductionmentioning
confidence: 99%